2021
DOI: 10.1007/s00439-021-02397-7
|View full text |Cite
|
Sign up to set email alerts
|

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity

Abstract: The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 49 publications
3
49
0
Order By: Relevance
“…Yet, other studies have brought supporting evidence for the implication of type I IFN-independent genes as monogenic etiologies of COVID-19. For example, genetic variants in the CFTR gene, including those causing cystic fibrosis, have been found to be overrepresented among critically ill COVID-19 patients [ 18 20 ], consistent with previous associations of the gene with susceptibility to respiratory tract infections [ 21 ]. Likewise, a genetic polymorphism in the androgen receptor ( AR ) gene that correlates with low serum testosterone level has been associated with severe COVID-19 in men [ 22 ].…”
Section: Monogenic Predisposition To Covid-19supporting
confidence: 76%
“…Yet, other studies have brought supporting evidence for the implication of type I IFN-independent genes as monogenic etiologies of COVID-19. For example, genetic variants in the CFTR gene, including those causing cystic fibrosis, have been found to be overrepresented among critically ill COVID-19 patients [ 18 20 ], consistent with previous associations of the gene with susceptibility to respiratory tract infections [ 21 ]. Likewise, a genetic polymorphism in the androgen receptor ( AR ) gene that correlates with low serum testosterone level has been associated with severe COVID-19 in men [ 22 ].…”
Section: Monogenic Predisposition To Covid-19supporting
confidence: 76%
“…Of note, the lead variant (rs11385942) is located in an intergenic region spanning several genes ( SLC6A20, LZTFL1, CCR9, FYC O 1, CXCR6, XCR1 ) and at least two of them ( LZTFL1, CCR9 ) are closely located with the risk GA-allele of rs11385942 associated with increased expression in human lung cells of SLC6A20 and LZTFL1 . Subsequent studies confirmed the relevance of the 3p21.31 locus in COVID-19 susceptibility and prognosis considering the presence of ancient DNA introgressed from Neanderthal populations ( Zeberg and Paabo, 2020 , 2021 ; Huffman et al, 2022 ) and highlighted additional genetic loci as well as rare variants involved in disease predisposition and prognosis ( Benetti et al, 2020 ; COVID-19 Host Genetics Initiative, 2021 ; Nakanishi et al, 2021 ; Schmiedel et al, 2021 ; Fallerini et al, 2022 ) . Moreover, in a sex and gender perspective, male sex together with old age and presence of critical comorbidities including diabetes, hypertension and cardiovascular disease have been considered among the strongest features accounting for large part of the severe cases ( Bonaccorsi et al, 2020 ; Gemmati et al, 2020 ).…”
Section: Introductionmentioning
confidence: 76%
“…If the predictions of Barh et al [ 5 ] are correct and if we consider their “genetic remittance” hypothesis, where the SARS-CoV-2 genetic material may integrate in and/or disrupt the human genome, some human genes or chromosomes may be malfunctional, which would result in congenital/genetic disorder development in the offspring. Although, there are Genome-Wide Association Studies (GWAS) to understand the COVID-19 susceptible or resistance loci in humans [ 130 , 131 , 132 ], so far there is not much information available on whether the SARS-CoV-2 genetic material is integrated in the genome or disrupting it. However, an in vitro analysis suggested that transcribed SARS-CoV-2 RNA may potentially integrate into the genome of cultured human cells [ 133 ] indicating the possibility of Barh et al’s hypothesis.…”
Section: Multi-omics-based Predicted Congenital Anomalies and Genetic...mentioning
confidence: 99%